2022
DOI: 10.3389/fcimb.2022.824860
|View full text |Cite
|
Sign up to set email alerts
|

Six Bacterial Vaginosis-Associated Species Can Form an In Vitro and Ex Vivo Polymicrobial Biofilm That Is Susceptible to Thymbra capitata Essential Oil

Abstract: Bacterial vaginosis (BV) is associated with serious gynaecologic and obstetric complications. The hallmark of BV is the presence of a polymicrobial biofilm on the vaginal epithelium, but BV aetiology is still a matter of debate. We have previously developed an in vitro biofilm model that included three BV-associated species, but, up to now, no studies are available whereby more bacterial species are grown together to better mimic the in vivo situation. Herein, we characterized the first polymicrobial BV biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…In two other similar studies by the same group, this EO was also found to present an important biomass removal effect on preformed Candida spp. biofilms (of 13 clinical isolates that belonged to four different species) [ 40 ], as well as a preformed polymicrobial biofilm that consisted of six cultivable bacterial vaginosis-associated bacterial species [ 41 ]. In another study, the EO from Italian C. capitatus at 1% v / v was found to inhibit biofilm formation and reduce preformed biofilms in about half of eleven clinical P. aeruginosa isolates from cystic fibrosis patients [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two other similar studies by the same group, this EO was also found to present an important biomass removal effect on preformed Candida spp. biofilms (of 13 clinical isolates that belonged to four different species) [ 40 ], as well as a preformed polymicrobial biofilm that consisted of six cultivable bacterial vaginosis-associated bacterial species [ 41 ]. In another study, the EO from Italian C. capitatus at 1% v / v was found to inhibit biofilm formation and reduce preformed biofilms in about half of eleven clinical P. aeruginosa isolates from cystic fibrosis patients [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that organic agricultural systems are more profitable and more environmentally friendly than conventional farming and deliver equivalent or higher-quality products that contain less (or no) pesticide residues [ 35 ]. While there are some previous antimicrobial and antibiofilm studies employing the EO from this aromatic and medicinal species [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], wild plants have most of the times been used to extract the oil. In addition, to the best of our knowledge, no other study has ever tested the action of T. capitatus EO against the biofilms of the aforementioned three important pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…These include plant extracts, such as Prangos ferulacea, Myrtus communis , Zataria multiflora , essential oils, small antimicrobial peptides of animal origin, bacteriocins and various groups of plant compounds (such as triterpenoids, phenols, and flavonoids) with antimicrobial and antiviral activity 46 , 48 . In particular, studies conducted by Machado and Rosca 25 , 32 demonstrated the potential use of Thymbra capitata essential oil (EO) as a novel therapeutic agent in the treatment of BV thanks to its antimicrobial effect against several bacterial species associated with BV including Gardnerella species. The natural products can be used in combination with MET or probiotics to improve the efficacy of antimicrobial therapy and reduce the recurrence of vaginal infections 43 .…”
Section: Discussionmentioning
confidence: 99%
“…As biofilms allow Gardnerella spp. to persist in recurrent BV, it is important to identify new treatments capable to counteract BV-biofilm 24 , 25 . Currently, the therapeutic agents available for the management of BV are topical agents containing lactic acid, clindamycin and/or orally administered antibiotics 26 , among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation